The true confessions of Charlotte Doyle - Avi, 1937- (New York : Scholastic Inc., 2003)
As the lone "young lady" on a transatlantic voyage in 1832, Charlotte learns that the captain is murderous and the crew rebellious.
Keywords: Sea stories; Mutiny -- Juvenile fiction; Sex role -- Juvenile fiction; Self-perception -- Juvenile fiction; Ships -- Juvenile fiction; Sea stories -- Juvenile fiction